1999
DOI: 10.1074/jbc.274.19.13305
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Novel Injury-regulated Genes

Abstract: To gain insight into the molecular mechanisms underlying the wound repair process, we searched for genes that are regulated by skin injury. Using the differential display reverse transcription-polymerase chain reaction technique, we identified a gene that was strongly induced as early as 12 h after wounding. Sequence analysis revealed the identity of the corresponding protein with skeletal muscle nascent polypeptide-associated complex (skNAC), a recently identified muscle-specific transcription factor. By in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…Yotov and St-Arnaud have also published that ␣NAC binds to a highly redundant consensus DNA sequence and thereby is implicated in transcription activation (25). Consistent with this idea, it has been reported that a tissue-specific isoform of ␣NAC (skNAC) is up-regulated in differentiating myoblasts and osteoblasts and in cells involved in wound healing (24,25,39,40). Note, however, that all biochemical activities reported up to now have been for ␣NAC and not skNAC.…”
Section: Discussionmentioning
confidence: 53%
“…Yotov and St-Arnaud have also published that ␣NAC binds to a highly redundant consensus DNA sequence and thereby is implicated in transcription activation (25). Consistent with this idea, it has been reported that a tissue-specific isoform of ␣NAC (skNAC) is up-regulated in differentiating myoblasts and osteoblasts and in cells involved in wound healing (24,25,39,40). Note, however, that all biochemical activities reported up to now have been for ␣NAC and not skNAC.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to HSP90, SmyD1 may interact with other proteins to regulate gene expression and muscle cell differentiation. SmyD1 interacts with skNAC, a heart and muscle-specific transcription factor involved in muscle regeneration (51)(52)(53). Moreover, SmyD1 represses gene transcription in an HDAC-dependent manner (22).…”
Section: Smyd1a and Smyd1bmentioning
confidence: 99%
“…Further studies suggested that skNAC functions as a transcriptional coactivator (18). skNAC has been implicated in controlling myogenic differentiation, and skNAC transcripts are expressed at high levels only in skeletal and cardiac muscle (18,19). skNAC mRNA is also induced in myoblasts of the panniculus carnosus within 12 h following skin injury, a finding that may reflect an early role for skNAC in muscle repair (19).…”
mentioning
confidence: 96%
“…m-Bop and skNAC Are Induced and Colocalize during Skeletal Myogenesis-Previous studies have shown that skNAC transcripts are induced early during skeletal myogenesis (18,19). Having obtained evidence for interaction of m-Bop isoforms and skNAC, we examined the kinetics of expression and localization of m-Bop and skNAC in differentiating C2C12 myoblasts.…”
Section: M-bop and Sknac Interact In The Yeastmentioning
confidence: 99%
See 1 more Smart Citation